Rare De Novo IGF2 Variant on the Paternal Allele in a Patient With Silver–Russell Syndrome - Xia, Chun-Ling; Lyu, Yuan; Li, Chuang; Li, Huan; Zhang, Zhi-Tao; Yin, Shao-Wei; Mao, Yan; Li, Wen; Kong, Ling-Yin; Liang, Bo; Jiang, Hong-Kun; Li-Ling, Jesse; et al. (Frontiers in Genetics, 2019)
Silver-Russell syndrome (SRS) is a rare, well-recognized disorder characterized by growth restriction, including intrauterine and postnatal growth. Most SRS cases are caused by hypomethylation of the paternal imprinting center 1 (IC1) in chromosome 11p15.5 and maternal uniparental disomy in chromosome 7 (UPD7). Here, we report on a Chinese family with a 4 year old male proband presenting with low birth weight, growth retardation, short stature, a narrow chin, delayed bone age, and speech delays, as a result of a rare molecular etiology. Whole-exome sequencing was conducted, and a novel de novo IGF2 splicing variant, NM_000612.4: c.157+5G>A, was identified on the paternal allele. In vivo functional analysis by RT-PCR and Sanger sequencing revealed that the variant leads to an aberrant RNA transcript lacking exon 2. Our results further confirm the IGF2 variant mediates SRS and expand the pathogenic variant and phenotypic spectrum of IGF2-mediated SRS. The results indicate that, beyond DNA methylation and UPD7 and CDKN1C variant tests, IGF2 gene screening should also be considered for SRS molecular diagnoses.